2014
DOI: 10.1111/1462-2920.12551
|View full text |Cite
|
Sign up to set email alerts
|

Differential stress resistance and metabolic traits underlie coexistence in a sympatrically evolved bacterial population

Abstract: Following intermittent batch growth in Luria-Bertani (LB) broth for about 1000 generations, differentially evolved forms were found in a population of Escherichia coli cells. Studies on this population revealed the emergence of key polymorphisms, as evidenced by analysis of both whole genome sequences and transcription analysis. Here, we investigated the phenotypic nature of several key forms and found a remarkable (interactive) coexistence of forms which highlights the presence of different ecological roles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The Cre-loxP or FLP-FRT marker rescue system can be easily used in natural S. cerevisiae and E. coli strains avoiding screening of auxotrophs [ 38 , 39 ]. Recent studies on natural populations and experimental evolution of E. coli identified strains exhibiting special properties, including tolerance to environmental stresses, utilization of particular carbon sources such as galactose, and low toxicity [ 40 , 41 ]. Based on this study and the background knowledge, we suggested that specific strains of model microorganisms can be used as bioengineering hosts for special applications.…”
Section: Discussionmentioning
confidence: 99%
“…The Cre-loxP or FLP-FRT marker rescue system can be easily used in natural S. cerevisiae and E. coli strains avoiding screening of auxotrophs [ 38 , 39 ]. Recent studies on natural populations and experimental evolution of E. coli identified strains exhibiting special properties, including tolerance to environmental stresses, utilization of particular carbon sources such as galactose, and low toxicity [ 40 , 41 ]. Based on this study and the background knowledge, we suggested that specific strains of model microorganisms can be used as bioengineering hosts for special applications.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the possible potential of natural strain as a bioengineering host, detailed background studies must first be carried out so as to avoid futile adventure. This is because genetic manipulation may not be as easy as observed in model strains (Puentes‐Tellez & van Elsas, 2015; Wang, Li, & Wang, 2016).…”
Section: Challenges Of Yeast Strains Developmentmentioning
confidence: 99%
“…be as easy as observed in model strains(Puentes-Tellez & van Elsas, 2015;Wang, Li, & Wang, 2016).Having overcome the choice of feedstock and yeast strain to engineer for bioethanol production, employing the right strategy for strain development is key. Various engineering techniques have been used for yeast strain development either for improved substrate utilization, increased stress, toxic and thermo-tolerance abilities, or improved bioethanol production.…”
mentioning
confidence: 99%